E-books and their impact on the educational sector (Herald of Journalism, 2025)
In the 21st century, e-books, which began their existence in the 1970s, are becoming an essential aspect of human existence. They are currently supported by practically all technological gadgets and are becoming more and more accessible to readers. In addition to examining the rise of e-books, this study aims to evaluate how they are used in the classroom, specifically by students and secondary school students. E-books have created new avenues for education and personal growth. The ability to access them at any time and from any location has increased the flexibility and accessibility of the learning process. A comprehensive review of scientific publications on the subject was carried out in order to carry out the study. Analysis was done on data regarding e-book usage in academic settings. The study's findings suggest that using e-books can boost literacy, boost student enthusiasm, and increase access to learning materials. However, it's important to remember the restrictions brought on by technical issues and eye strain. Even with the widespread digitization and advancement of e-books, more research is still needed on the subject of this study because e-books hold great promise for modernizing the educational system.
Keywords: e-books, Project Gutenberg, education, libraries, digitalization, literacy.